Dollarization and Maturity Structure of Public Securities : The Experience of Bolivia - Vesperoni, Esteban; Orellana R., Walter (Washington, D.C. : International Monetary Fund, 2008)
The public debt profile has improved in Bolivia in recent years, with regard to both the maturity structure and the currency composition. This paper analyzes changes in the public debt profile in Bolivia since 2000, and the role played by macroeconomic factors and the debt management strategy adopted by the authorities. We find that both played an important role, in particular the strengthening of the fiscal and international reserves positions and the appreciation of the Boliviano; and regulations promoting the use of the domestic currency. Our findings are consistent with Claessens, Klingebiel and Schmukler (2007)-who found that macro and institutional factors had an impact on debt profiles for a group of emerging and developed economies-and are in contrast with the original sin literature, which stresses that profiles are mainly determined by market incompleteness. We also compare the debt profile of Bolivia with those of other countries in Latin America, and find that there is still room for improvement against the regional benchmark, both in terms of maturity structure and currency composition.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet